Ear, Nose, Throat and Head and Neck Surgery Activity in Tertiary Care Center during COVID-19 Pandemic - Rijal, Krishna Chandra; Koirala, Krishna Prasad; Karki, Bikram Babu; Maharjan, Manita (Journal of College of Medical Sciences-Nepal, 2021)
Introduction: Corona virus disease 2019 (COVID 19) is an infectious respiratory disease caused by the novel virus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Till 31st August 2020, 39460 COVID-19 positive cases confirmed and 228 deaths occurred in Nepal. The surgical activities in the division of ENT and HNS (Ear, Nose, Throat and Head and Neck Surgery) across the world has been affected with many hospitals confining themselves to only emergency or essential surgeries due to implementation of lockdown by many countries. Manipal Teaching Hospital being a tertiary care referral centre in western Nepal has wide array of cases coming from various parts of the country and due to the pandemic the surgical activity of our ENT and HNS unit has undergone profound changes. Methods: A six months prospective study of “ENT and HNS Surgical Activity in Tertiary Care Center during COVID-19 Pandemic” was conducted in the department of ENT and HNS, Manipal college of Medical Sciences, Pokhara, Nepal. Statistical analysis of the study was done for various parameters like age, sex, incidence and types of elective and emergency surgeries and comparing the frequency of surgeries done during the COVID-19 pandemic vs that during the same period in the previous year. Results: This study includes a total of 56 surgery cases out of which 26 were emergency and 30 were elective. Among 26 emergency cases, five were ear, one was nose, nine were throat and 11 were head & neck cases. Similarly, among 30 elective cases, six were ear, eight were nose, 11 were throat and five were head & neck cases. The most commonly performed emergency cases were incision and drainage of abscess followed by repair of wounds and rigid oesophagoscopy and removal of foreign body. Commonly performed elective cases were excision of ENT and HNS lesions followed by Functional endoscopic sinus surgery. Conclusions: The COVID-19 pandemic caused a steep decrease in ENT and HNS surgical activities both the elective and emergency surgery.